Augustine and the phenomenological tradition - Biebighauser, Jeffrey (2012)
This essay traces the reception of Augustine in the 20th and 21st century phenomenological tradition. It gives special attention to recent monographs on Augustine by Jean-Luc Marion and Jean-Louis Chrétien, but contextualises these both fore (by examining the earlier work of Edmund Husserl and Martin Heidegger, as well as earlier and less determinative Augustinian engagements by Marion and Chrétien) and aft (by critically considering the philosophical, philological and theological implications of phenomenology for the study of Augustine). The cross-fertilization of its study of Augustine himself and its study of the various phenomenological appropriations of Augustine sheds new light on the Augustinian questions of Platonism, ontology, and the role of Scripture in philosophy.